An exploration and description of experiences of at-risk youth in a correctional center in Eswatini regarding a resilience intervention program - Shabangu, Sifiso B.; Koen, Vicki (Frontiers in Psychology, 2022)
Resilience-focused programmes advocate nurturing positive adoptive traits to inform prevention and intervention efforts. Considering that no resilience intervention programmes have been developed specifically for at-risk youth in correctional centres in Eswatini, the authors developed a programme with this focus through a combination of literature review and earlier empirical research with correctional officers and youth in a correctional centre in Eswatini. This study aimed to evaluate the programme through exploration and description of experiences of at-risk youth in a correctional centre in Eswatini regarding the programme. A purposive sample of 16 youths in a correctional centre in Eswatini participated in a World Café, and data were analysed thematically. Three themes were identified: Positive outcomes of participation, challenges encountered in the programme, and recommendations for the programme.